2016
DOI: 10.1049/iet-nbt.2015.0059
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis and antimicrobial activity of silver nanoparticles using wild medicinal mushroomGanoderma applanatum(Pers.) Pat. from Similipal Biosphere Reserve, Odisha, India

Abstract: In the present study, green synthesis and cost effective approach of silver nanoparticles using wild medicinal mushroom Ganoderma applanatum (Pers.) Pat. from Similipal Biosphere Reserve, Odisha, India is reported. The biosynthesised AgNPs were characterised using UV-visible spectroscopy, particle analyser and scanning electron microscopy studies. It was found by dynamic light scattering analysis, that the average size and charges of the AgNPs were 133.0 ± 0.361 nm and -6.01 ± 5.30 mV, respectively. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…Silver is recognized for its anti-microbial activity against a broad spectrum of pathogenic microorganisms (Mohanta et al, 2016b). Silver (Ag) has been used since ancient times for its medicinal properties and now the activity and application of silver nanoparticles (AgNPs) is being explored in medical research.…”
Section: Introductionmentioning
confidence: 99%
“…Silver is recognized for its anti-microbial activity against a broad spectrum of pathogenic microorganisms (Mohanta et al, 2016b). Silver (Ag) has been used since ancient times for its medicinal properties and now the activity and application of silver nanoparticles (AgNPs) is being explored in medical research.…”
Section: Introductionmentioning
confidence: 99%
“…Mukherjee’s group reported that the aqueous extract of naturally occurring edible mushroom Volvariella volvacea acts as a reducing and capping agent during extracellular synthesis of Au, Ag and Au–Ag nanoparticles [ 15 ]. Recently our group has reported the synthesis of AgNPs using extracts of Ganoderma lucidum and Ganoderma applanatum both known for their medicinal properties exhibiting higher antimicrobial activities [ 16 ]. The aqueous extract of edible oyster mushrooms ( Pleurotus florida ) has also been shown to be a potential reducing agent during the photo-irradiated extracellular synthesis of silver nanoparticles [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also tested the stability for a week, and the prepared nanoparticles were stable. This may be one of the reasons why the particle shows better performance when it is introduced with cancer cells [ [26] , [27] , [28] ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%